2017
DOI: 10.1080/19415257.2017.1287767
|View full text |Cite
|
Sign up to set email alerts
|

Developing the developers: supporting and researching the learning of professional development facilitators

Abstract: Research on teacher professional development is extensive but there are fewer studies about the practitioners who facilitate professional development. Here we report on a pilot programme for professional development facilitators rooted in a cycle of action research.Informed by a categorisation of professional knowledge and skills of facilitators, in the 'developing the developers' programme, professional development facilitators enquired collaboratively into their practice using video observation and peer revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 50 publications
0
46
0
2
Order By: Relevance
“…[Teacher, School D] In these change sequences the focus shifts from an individual teacher to the wider school, as new and adapted curriculum materials support the adoption of new practices by colleagues. We use 'social domain' (Perry and Boylan 2018) here to differentiate interaction between colleagues from interactions with the facilitators of the PD programme (the external domain).…”
Section: Change Sequence 1: External To Practicementioning
confidence: 99%
“…[Teacher, School D] In these change sequences the focus shifts from an individual teacher to the wider school, as new and adapted curriculum materials support the adoption of new practices by colleagues. We use 'social domain' (Perry and Boylan 2018) here to differentiate interaction between colleagues from interactions with the facilitators of the PD programme (the external domain).…”
Section: Change Sequence 1: External To Practicementioning
confidence: 99%
“…To be a facilitator therefore requires the deployment of various categories of knowledge and skills relating to each of these aspects of the role. We have previously suggested (Perry & Boylan, 2017) that the learning needs of professional development facilitators can be grouped into three categories: knowledge and skills for teaching (classroom pedagogical approaches, subject and curriculum knowledge), facilitation skills and knowledge (how to organise and support the learning of experienced teachers), and knowledge about professional development (theoretical and practical models of professional development, teacher learning and evaluation). In that previous study, we offered a model of learning for professional development facilitators.…”
Section: Building Capacity For Professional Developmentmentioning
confidence: 99%
“…In a previous study (Perry & Boylan, 2017), it was proposed that professional development facilitators may also benefit from learning knowledge of professional development, including understanding theoretical models of how teachers learn, models of professional development such as practitioner research strategies and models of evaluation. Other studies have also shown that expert facilitators draw on this type of knowledge (Cordingley, et al, 2015).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the critical review of the level models literature has been used in a number of publications (for example, Earley and Porritt, 2014;Perry and Boylan, 2017;McChesney and Aldridge, 2018; and an extended consideration by . The critique of Guskey's model in particular has been quite widely used (e.g.…”
Section: R3: Coldwell and Simkins 2011mentioning
confidence: 99%